The Frequency-Dependent Aerobic Exercise Effects of Hypothalamic GABAergic Expression and Cardiovascular Functions in Aged Rats - Li, Yan; Zhao, Ziqi; Cai, Jiajia; Gu, Boya; Lv, Yuanyuan; Zhao, Li (Frontiers in Aging Neuroscience, 2017)
A decline in cardiovascular modulation is a feature of the normal aging process and associated with cardiovascular diseases such as hypertension and stroke. Exercise training is known to promote cardiovascular adaptation in young animals and positive effects on motor and cognitive capabilities, as well as on brain plasticity for all ages in mice. Here, we examine the question of whether aerobic exercise interventions may impact the GABAergic neurons of the paraventricular nucleus (PVN) in aged rats which have been observed to have a decline in cardiovascular integration function. In the present study, young (2 months) and old (24 months) male Wistar rats were divided into young control, old sedentary, old low frequency exercise (20 m/min, 60 min/d, 3 d/w, 12 w) and old high frequency exercise (20 m/min, 60 min/d, 5 d/w, 12 w). Exercise training indexes were obtained, including resting heart rate, blood pressure, plasma NE, and heart weight-to-body weight ratios. The brain was removed and processed according to the immunofluorescence staining and western blot used to analyze the GABAergic terminal density, the proteins of GAD67, GABAA receptor and gephyrin in the PVN. There were significant changes in aged rats compared with those in the young control. 12 w aerobic exercise training has volume-dependent ameliorated effects on cardiovascular parameters, autonomic nervous activities and GABAergic system functions. These data suggest that the density of GABAergic declines in the PVN is associated with imbalance in autonomic nervous activities in normal aging. Additionally, aerobic exercise can rescue aging-related an overactivity of the sympathetic nervous system and induces modifications the resting BP and HR to lower values via improving the GABAergic system in the PVN.